Comparison between blood pressure during obstructive respiratory events in REM and NREM sleep using pulse transit time - Aljohara S. Almeneessier (Nature Portfolio, 2020)
Abstract Rapid eye movement-predominant obstructive sleep apnea has been shown to be independently associated with hypertension. This study aimed to non-invasively measure blood pressure during the rapid eye movement (REM) and non-rapid eye movement (NREM) obstructive events and the post-obstructive event period. Thirty-two consecutive continuous positive airway pressure-naïve obstructive sleep apnea patients (men, 50%) aged 50.2 ± 12 years underwent overnight polysomnography. Blood pressure was assessed indirectly using a validated method based on the pulse transit time and pulse wave velocity during the NREM and REM obstructive events (both apneas and hypopneas) and the post-obstructive event period. Among the recruited patients, 10 (31.3%) had hypertension. Mean apnea-hypopnea index was 40.1 ± 27.6 events/hr. Apnea-hypopnea indexes were 38.3 ± 30.6 and 51.9 ± 28.3 events/hr for NREM and REM sleep, respectively. No differences were detected in obstructive respiratory event duration or degree of desaturation between REM and NREM sleep. Additionally, no difference in blood pressure (systolic and diastolic) was detected between REM and NREM sleep during obstructive events and post-obstructive event period. Simple linear regression identified history of hypertension as a predictor of increased systolic blood pressure during obstructive events and post-obstructive event period in both rapid eye movement and non-rapid eye movement sleep. Oxygen desaturation index was also a predictor of increased systolic blood pressure during obstructive events and post-obstructive event period in REM sleep. When obstructive event duration and the degree of desaturation were comparable, no difference in blood pressure was found between REM and NREM sleep during obstructive events and post-obstructive event period.